Chemical characteristics of native soil in shrimp Gher and agricultural land - Bala, Ashis Kumar; Bari, Quazi Hamidul; Ahsan, Amimul; ElSergany, Moetaz Mahmoud; Sathyamurthy, Ravishankar; Bek, Mohamed Ali; Rowshon, Md Kamal; Mallick, Jayanta; Nik Daud, Nik Norsyahariati (Faculty of Engineering, Chulalongkorn University, 2016)
This study was conducted to characterize the native soil at shrimp Gher and agricultural land in Khulna, Bangladesh. Eight locations were selected and among them five Ghers from south part of Dumuria which is about 60 km away from KUET campus, Khulna, Bangladesh. In the laboratory, various parameters such as salinity, organic content, chloride, pH, alkalinity, conductivity and moisture content were determined by following standard methods. The chloride and alkalinity were determined manually and pH, conductivity and salinity were determined by digital meter. The organic and moisture content both were highest at 30 cm depth for both the cases of shrimp Gher and agricultural land. Chloride was highest at 15 cm depth for both the cases shrimp Gher and agricultural land. Alkalinity was highest at 30 cm depth for shrimp Gher, however, the lowest was for agricultural land. It is concluded that the salinity and organic content vary with depth, age and soil condition.